KESESUAIAN PERESEPAN OBAT DENGAN FORMULARIUM RUMAH SAKIT PADA PASIEN BPJS POLI JANTUNG DI RUMAH X, KOTA BEKASI, PERIODE JANUARI – JUNI 2023 - Mariyana, Tyssa; Bachtiar, Wahyu; Imawati, Cory; Kusumadewi, Ariyanti (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2025)
The Hospital Formulary is the drugs accepted and approved by the Pharmacy and Therapeutics Committee for use in hospitals for a certain period of time. The hospital list includes cardiovascular diseases. Worldwide, cardiovascular disease is the number one cause of death after cancer. This research method is a descriptive non-experimental research. . Data were collected retrospectively, namely by observing and evaluating the prescription sheets of outpatients with BPJS insurance for 6 months, namely January 2023 - June 2023. The average suitability of prescriptions from January - June 2023 is 83.80% and this is still far from the standard of suitability of prescriptions based on the formulary which should be 100% this is due to the presence of a new cardiologist and there has been no change in the hospital formulary for 2023. Demographic data based on gender in patients suffering from CHD patients with male gender every month have the highest percentage compared to female gender. This is because the risk factor for suffering from CHD in men is greater. Meanwhile, the top ten drugs that are not in accordance with the Hospital Formulary at X Hospital in Bekasi city are Brillinta 90 mg tablets (43.75%).